Compound‐Specific Radiocarbon Analysis of (Sub‐)Antarctic Coastal Marine Sediments—Potential and Challenges for Chronologies. Issue 10 (9th October 2020) - Berg, S.; Jivcov, S.; Kusch, S.; Kuhn, G.; Wacker, L.; Rethemeyer, J.
Abstract: In Antarctic and Subantarctic environments, 14 C‐based age determination is often challenging due to unknown reservoir effects, low organic carbon contents of sediments, and high contributions of petrogenic ( 14 C‐free) carbon in ice marginal settings. In this study, we evaluate possible benefits and challenges of compound‐specific radiocarbon analysis (CSRA) as a tool for age determination of marine Antarctic and Subantarctic sediment sequences. We present a comprehensive data set of 14 C ages obtained on bulk organic carbon, carbonates, and on fatty acids (FA) from three coastal marine sediment cores from Subantarctic South Georgia and East Antarctica. Low molecular weight (LMW) FA represent the least 14 C‐depleted fraction, indicating that the phytoplankton‐derived compounds can be a means of dating sediments. In contrast, vascular plant‐derived high molecular weight FA are systematically depleted in 14 C relative to the low molecular weight homologues, reflecting processes such as soil formation/erosion in the catchment. Comparative age‐depth models show significant differences, depending on the material used for the respective models. While the land plant‐derived FA may lead to an overestimation of the actual sediment age, LMW FA reveal complex aquatic reservoir effects. Bulk sedimentary organic carbon 14 C ages likely provide appropriate age estimates in settings with low petrogenic carbon input in the Antarctic, whereas CSRA has the potential to produce improved age control in settings with high contributions of petrogenic carbon. Key Points: Phytoplankton‐derived low molecular weight fatty acids can be used to date Antarctic marine sediments Contribution of petrogenic, reworked carbon in Antarctic and Subantarctic shelf settings can be assessed by compound‐specific radiocarbon analysis Land plant‐derived high molecular weight fatty acids in the Subantarctic are systematically depleted in radiocarbon